(untitled) (Research, Society and Development, 2024)
It is possible to identify competent psychotherapists from those who are not. The theory of multicultural competence has been able to explain why some psychotherapists perform better than others when working with black people. The objective of this study was to explore, through thematic analysis, the performance of psychologists and their special/specific skills to practice psychotherapy with black people, as well as to reflect on problems that commonly appear in this work, based on their responses about their perception of working with black patients/clients and other intersectionality’s that cross these racialized subjectivities. The sample consisted of 163 psychotherapists who were invited to elucidate their perceptions and experiences regarding psychotherapy with black patients, based on the following triggering questions: (1) for those who do not have black patients, identify the reasons; (2) perception or not of differences between white and black patients and, if so, an indication of these differences; (3) assessment of whether psychotherapy with black people requires special/specific skills and what these would be, if so - and, if not, explanation of the reasons why they understand that these special/specific skills are not necessary; (4) recommendations for psychotherapeutic work with people from cultures/experiences that differ from the normative standard, such for example, racialized groups, the LGBTQIA+ community, immigrants and/or refugees, people with disabilities and/or special needs. It was possible to verify that it is necessary to deepen the theoretical and practical knowledge of psychotherapists about multicultural competencies in Psychotherapy with black clients/patients.